2022
DOI: 10.3390/brainsci12081045
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Verticalization plus Music Therapy in Chronic Disorders of Consciousness: Promising Results from a Pilot Study

Abstract: Background: Music stimulation is considered a valuable form of intervention in disorders of consciousness (DoC); for instance, verticalization may improve motor and cognitive recovery. Our purpose is to investigate the effects of a novel rehabilitative approach combining robotic verticalization training (RVT) with personalized music stimulation in people with DoC. Methods: Sixteen subjects affected by minimally conscious state due to traumatic brain lesions who attended our Intensive Neuro-Rehabilitation Unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Among the 26 articles included in this review, we found only 2 articles [ 12 , 24 ] on the use of robotic verticalization with the Erigo device in sTBI patients. Specifically, De Luca et al [ 12 ] administered autobiographical music stimulation plus robotic verticalization to the experimental group with a better improvement in the level of awareness and consciousness.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 26 articles included in this review, we found only 2 articles [ 12 , 24 ] on the use of robotic verticalization with the Erigo device in sTBI patients. Specifically, De Luca et al [ 12 ] administered autobiographical music stimulation plus robotic verticalization to the experimental group with a better improvement in the level of awareness and consciousness.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 26 articles included in this review, we found only 2 articles [ 12 , 24 ] on the use of robotic verticalization with the Erigo device in sTBI patients. Specifically, De Luca et al [ 12 ] administered autobiographical music stimulation plus robotic verticalization to the experimental group with a better improvement in the level of awareness and consciousness. Taveggia et al [ 24 ] found that the use of the Erigo device may reduce orthostatic hypotension in vs. and MCS patients, thanks to its gradual verticalization and stepping, with constant and non-invasive monitoring of vitals parameters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations